Penerapan Logika Fuzzy dalam Sistem Pakar Deteksi Hama dan Penyakit Tanaman Kakao Kecamatan Wulanggitang Flores Timur - Soge, Fransiskus Pati; Deta, Bernadete; Watomakin, Dominikus Boli (Jurnal Kridatama Sains dan Teknologi, 2024)
An expert system for detecting types of pests and diseases on cocoa plants must be carried out quickly and accurately, because diseases in cocoa plants can quickly spread and attack all other agricultural land. This research aims to describe the application of the fuzzy logic method in a website-based expert system to detect pests and diseases of cocoa plants in Wulanggitang sub-district, East Flores, NTT which will provide practical benefits for the community and local government as well as theoretically for the development of knowledge for experts who are expected to be able to detecting pests and diseases of cocoa plants in Wulanggitang sub-district, East Flores, NTT through the application of fuzzy logic methods in a website-based expert system. This research method is through developing a running system with stages of communication, planning, modeling, construction and deployment. Data collection methods were carried out through observation and interviews. The research results showed that the expert system was successfully built by applying the concept of website-based fuzzy logic theory to detect pests and diseases of cocoa plants and how to control them. The results of implementation and testing on fuzzy logic modeling with accuracy testing values and black box testing results obtained satisfactory results. This indicates that the system being built is ready to be used.